Formulation of Aluminum Chloride Phthalocyanine in Pluronic™ P‐123 and F‐127 Block Copolymer Micelles: Photophysical properties and Photodynamic Inactivation of Microorganisms. (6th February 2015) - Vilsinski, Bruno Henrique; Gerola, Adriana Passarella; Enumo, Junior Adalberto; Campanholi, Katieli da Silva Souza; Pereira, Paulo Cesar de Souza; Braga, Gustavo; Hioka, Noboru; Kimura, Elza; Tessaro, André Luiz; Caetano, Wilker
Abstract Aluminum Chloride Phthalocyanine (AlPcCl) can be used as a photosensitizer (PS) for Photodynamic Inactivation of Microorganisms (PDI). The AlPcCl showed favorable characteristics for PDI due to high quantum yield of singlet oxygen (ΦΔ) and photostability. Physicochemical properties and photodynamic inactivation of AlPcCl incorporated in polymeric micelles of tri‐block copolymer (P‐123 and F‐127) against microorganisms Staphylococcus aureus, Escherichia coli and Candida albicans were investigated in this work. Previously, it was observed that the AlPcCl undergoes self‐aggregation in F‐127, while in P‐123 the PS is in a monomeric form suitable for PDI. Due to the self‐aggregation of AlPcCl in F‐127, this formulation did not show any effect on these microorganisms. On the other hand, AlPcCl formulated in P‐123 was effective against S. aureus and C. albicans and the death of microorganisms was dependent on the PS concentration and illumination time. Additionally, it was found that the values of PS concentration and illumination time to eradicate 90% of the initial population of microorganisms (IC90 and D90, respectively) were small for the AlPcCl in P‐123, showing the effectiveness of this formulation for PDI.